Synthesis, Structure, Gas‐Phase Reactivity, and Catalytic Relevance of Trinuclear Mo3S4 Clusters Bearing Terminal Hydroxo and Hydrosulfido Groups. Issue 33 (25th September 2013) - Beltrán, Tomás F.; Feliz, Marta; Llusar, Rosa; Safont, Vicent S.; Vicent, Cristian
Abstract: Molybdenum(IV) hydroxo [Mo3 S4 (dmpe)3 (OH)3 ] + (1 + ) and hydrosulfido [Mo3 S4 (dmpe)3 (SH)3 ] + (2 + ) [dmpe = 1, 2‐bis(dimethylphosphanyl)ethane] trimetallic cuboidal cluster complexes have been isolated in high yields by treating their chloride precursors with sodium hydroxide or sodium hydrosulfide, respectively. The crystal structures of [1 ]BPh4 and [2 ]PF6 confirm that –QH (Q = O, S) groups are coordinated to metal centers. Both hydroxo and hydrosulfido Mo3 S4 cluster complexes are fully characterized by spectroscopic, mass spectrometric, and X‐ray techniques. A comparative study of the gas‐phase dissociation of1 + and2 + cations using ESI tandem mass spectrometry is presented, and the results are compared with those already reported for the hydroxo tungsten analogue. The gas‐phase reactivity of1 + and2 + species towards ethanol and 1‐penthanethiol have been explored. The gas‐phase‐generated [Mo3 S4 (dmpe)2 (O)(OH)] + cation activates ethanol molecules through a similar mechanism to that proposed for its tungsten congener. The main differences in aldehyde elimination under collision‐induced dissociation (CID) conditions between molybdenum and tungsten cluster sulfides are discussed. Abstract : Two molybdenum(IV) hydroxo and hydrosulfido cuboidal cluster complexes have been synthesized. Bonding is discussed on the basis of crystallographic and spectroscopic characterization. A comparative study of their gas‐phase dissociation and reactivity with ethanol and 1‐pentanethiol has been done using electrospray ionization and tandem mass spectrometry experiments and DFT calculations.